Maternal knowledge on nutritional-focused nurturing care and associated factors among women with stunted children aged 6-23 months in Yogyakarta, Indonesia: A cross-sectional study - Haryanti, Fitri; Hartini, Sri; Akhmadi; Andarwati, Fitriana; Risnawati, Hani; Pratiwi , Alissa Nur; Kusumawati, Ananda Sekar; Cahyani, Redyta Dwi; Lusmilasari, Lely (Belitung Nursing Journal, 2024)
Background: Childhood stunting poses serious long-term risks to cognitive development, education, and adult productivity. While research has explored stunting’s causes and effects, there is a lack of focus on maternal knowledge of nutrition-focused nurturing care for stunted children. This gap limits the ability to design effective interventions that target improved caregiving practices. Objective: This study aimed to assess maternal knowledge of nutrition-focused nurturing care and explore associated factors, including child gender, maternal age, education, income, and prior exposure to nurturing care information, among mothers of stunted children aged 6-23 months in Indonesia. Methods: A cross-sectional study was conducted with 73 mothers in Kulon Progo, Yogyakarta. Data were collected from February to March 2024 using a validated self-assessment questionnaire covering four domains: responsive caregiving, early learning opportunities, safety and security, and supportive caregiver well-being. Statistical analyses, including t-tests and one-way ANOVA, were performed. Results: Overall maternal knowledge of nurturing care was high, with a mean score of 25.15 (SD = 4.72). Factors significantly associated with higher knowledge included having male children (p = 0.017), being aged 30-34 years (p = 0.035), possessing higher education levels (p = 0.002), and prior exposure to nurturing care information (p <0.001). Family income significantly influenced knowledge in the domain of early learning opportunities (p = 0.006), though not in other areas. Conclusion: Maternal knowledge of nutrition-focused nurturing care was influenced by child gender, maternal age, education, income, and prior exposure to nurturing care information. These findings emphasize the importance of focused educational interventions in nursing practice to enhance maternal knowledge. Addressing these factors can help align nursing strategies better to support the healthy growth and development of children.